Psichologiceskie osobennosti vybora takticeskich rešenij gandbolistami vysokoj kvalifikacii - Taha, S.; Gillard, M. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The results of the research on the psychological features of choice of the tactical decisions by the highly qualified handball players are described in the article. On the basis of the conducted experimental researches, the authors have analyzed the results and drawn the conclusions.